EFEKTIVITAS BADAN PENDAPATAN DAERAH DALAM PENERIMAAN PAJAK DAERAH DI KOTA TANGERANG SELATAN - Assyodiq, Rizal; Sudarwanto, Sudarwanto (Jurnal Ilmu Administrasi Publik, 2024)
The aim of this research is to analyze and evaluate the effectiveness of the Regional Revenue Agency in Regional Tax Revenue in South Tangerang City as well as the obstacles and efforts to overcome these obstacles. This research uses a qualitative descriptive analysis approach. The data collection methods used were interviews, observation and literature study with 6 informants. The results of the research show that the effectiveness of the Regional Revenue Agency in Regional Tax Revenue in South Tangerang City has run smoothly and in accordance with applicable regulations. The obstacles found were a lack of public awareness of paying taxes, taxpayer reporting that was not in accordance with the real situation in the field, a lack of facilities and infrastructure, and a lack of human resources in the office. The solutions to these obstacles are to educate the public about the importance of paying taxes, improving facilities and infrastructure and increasing human resources.